2012
DOI: 10.1038/nature11607
|View full text |Cite
|
Sign up to set email alerts
|

B12 cofactors directly stabilize an mRNA regulatory switch

Abstract: Structures of riboswitch receptor domains bound to their effector have revealed how mRNAs recognize diverse small molecules, but mechanistic details into its linkage with regulation of gene expression remain elusive1,2. To address this, we solved crystal structures of two different classes of cobalamin (vitamin B12) binding riboswitches that include the structural switch of the downstream regulatory domain. These classes share a common cobalamin-binding core, but use distinct peripheral extensions to recognize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

19
279
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 187 publications
(301 citation statements)
references
References 40 publications
19
279
0
3
Order By: Relevance
“…Pathways. Upon interrogation of the remaining up-regulated genes, we observed that many have an association with B 12 -dependent metabolism and may be under the control of B 12 riboswitches, known for their ability to modulate transcription of downstream genes dependent on the presence of the B 12 ligand (13,14,(22)(23)(24). Nine putative gene clusters downstream of B 12 riboswitches had elevated expression in Cu-limited conditions (Fig.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Pathways. Upon interrogation of the remaining up-regulated genes, we observed that many have an association with B 12 -dependent metabolism and may be under the control of B 12 riboswitches, known for their ability to modulate transcription of downstream genes dependent on the presence of the B 12 ligand (13,14,(22)(23)(24). Nine putative gene clusters downstream of B 12 riboswitches had elevated expression in Cu-limited conditions (Fig.…”
Section: Resultsmentioning
confidence: 97%
“…However, N 2 O exhibits cytotoxicity, as it is known to bind to and inactivate vitamin B 12 (B 12 ), an essential cellular cofactor in B 12 -dependent enzymes involved in methionine and DNA synthesis (11,12). B 12 also acts as a ligand for B 12 riboswitches that modulate gene expression in the absence of this cofactor (13,14). The possible impact of environmental N 2 O emissions on B 12 metabolism in microbiological communities has largely been ignored.…”
mentioning
confidence: 99%
“…Other B 12 derivatives most commonly include methylcobalamin, cyanocobalamin, and aquocobalamin, which differ in their composition by their corrin ring (13). It was recently shown that methylcobalamin and aquocobalamin are also recognized by different cobalamin riboswitches where various RNA architectures are used to sense these B 12 derivatives (9). As reported for the S-adenosyl-* This work was supported in part by the Canadian Institutes of Health…”
mentioning
confidence: 99%
“…Mutagenesis experiments showed that residues forming the kissing loop interaction are important for ligand binding (10), consistent with the kissing loop being involved in genetic control. Recent crystal structures revealed that the bound ligand interacts weakly with the kissing loop ribose-phosphate backbone through van der Waals contacts (8,9). The kissing loop interaction was also shown to form in the absence of ligand at elevated Mg 2ϩ ion concentrations (9).…”
mentioning
confidence: 99%
See 1 more Smart Citation